Features of arterial hypertension course in patients with psoriasis - V. A. Vizir; G. I. Makurina (Zaporožskij Medicinskij Žurnal)
Risk of cardiovascular and cerebrovascular events development in psoriasis patients is higher than in population as a whole. Combination of arterial hypertension and psoriasis is widespread and understudied state, thus the objective of our work was to reveal features of this comorbid pathology formation and course.